THE ANALYSIS OF PASSIVE AGGRESSIVE BEHAVIOR ON ISLAMIC ADOLESCENT FROM SINGLE PARENT FAMILIES - Fauziah, Febriella; Netrawati, Netrawati; Neviyarni, Neviyarni; Nurfarhanah, Nurfarhanah (Psikis : Jurnal Psikologi Islami, 2023)
This study aims in general to describe the passive-aggressive behavior adolescents can develop from the parenting pattern of single-parent families. Adolescents who live with a single parent have a risk of delinquency compared to adolescents who are cared for by intact parents. The condition of adolescents who are raised by single parents causes children not to be used to expressing their thoughts and feelings freely. This type of research is quantitative research with a descriptive approach. Data analysis in this study was obtained through a passive-aggressive behavior questionnaire with a Likert scale with a sample of 36 students from single parent families at SMKN 1 Enam Lingkung. The results of the study show that passive-aggressive behavior is in the high category, which means that students have passive-aggressive behavior that needs to be intervened so that students can avoid maladaptive behavior. The school responding to that issue immediately by teachers in schools, especially BK teachers in the implementation of services to reduce passive-aggressive to help students develop more optimally.